Emotion dysregulation as cross-disorder trait in child psychiatry predicting quality of life and required treatment duration - Bierens, Margreet; Hartman, Catharina A.; Klip, Helen; Deckers, Stijn; Buitelaar, Jan; Rommelse, Nanda (Frontiers in Psychiatry, 2023)
Background: Emotion dysregulation (ED) is increasingly under investigation as a cross-disorder trait, and is by some considered as the core feature in mental disorders. The underlying assumptions are that ED is a trait that manifests similarly across disorders and with similar impact. The aims of this study are to examine the shared and specific features of ED in relation to DSM-categories in a large sample of clinically referred youth. Methods: Information on clinical diagnosis (Attention Deficit/Hyperactivity Disorder ADHD, Autism Spectrum Disorder, Oppositional Defiant Disorder/Conduct Disorder, Anxiety and Mood Disorders), ED (measured by the CBCL-Emotion Dysregulation Index), Quality of Life (Qol, measured by the Kidscreen-27), and treatment duration (measured by Electronic Health Records) was retrieved from two large samples of toddlers (1.5-5 year old; N=1,544) and school aged children (6-18 year old; N=7,259). Frequency scores and logistic regression were used to study symptom profiles of ED, as measured with CBCL-EDI, across all disorders. Linear regression was used to determine the predictive value of ED (CBCL-EDI total score) regarding QoL and treatment duration in addition to - and in interaction with - clinical diagnosis. Results: Across disorders, equal levels of total ED were found, which predicted lower QoL and a longer treatment duration in addition to clinical diagnosis. The majority of items (11/15 and 16/18) were of equal relevance to the disorders; items that were not, largely reflected disorder specific DSM definitions (i.e. externalizing symptoms in ODD/CD and internalizing symptoms in Anxiety and Mood disorders). Conclusions: ED is a clinically useful cross-disorder trait to predict severity of impairment as well as required treatment duration. In addition, ED is largely composed of shared features across disorders, with certain disorder specific coloured elements.